ACCRUAL ACCOUNTING & FINANCIAL REPORTING IN THE PUBLIC SECTOR TO ENHANCE ACCOUNTABILITY AND TRANSPARENCY (REFRAMING IMPLEMENTATION IN INDONESIA) - Nanang shonhadji (EKUITAS (Jurnal Ekonomi dan Keuangan), 2010)
Implementation modified cash basis at public sector in Indonesia have adopted to implement accrual accounting and financial reporting as the basis for their reformed accounting policy. Public administration in Indonesia has changed dramatically since 1999. The country has gone through one of the fastest and most comprehensive devolution reforms ever seen. Managerial and financial responsibilities have been decentralized from central government, mostly to local government at the district level. Under accrual accounting, government  reports  financial flows in terms of an operating statement equivalent to a business profit and loss statement. If the budget operating balance is  zero,  then  this  year's  operating  expenses  are  being  fully  covered  by this  year's  revenue. Expenses are not  the  same  as  outlays so expenses  measure  this  year's  costs  of production, whereas  outlays  does  not. Prior to the introduction of accrual accounting, the Indonesian government have fiscal policy indicator which underlying cash balance. It was the cash budget balance which the local government. With the arrival of accrual accounting, however, the cash budget balance has been supplanted in this context. This helps us to compare the cash budget balance with fiscal balance. This phenomenon has been widely debated in public management circles, and within the academic literature. Many of these debates however, have been arid and narrowly technically focused. This paper reviews the harmonization process of Indonesian local public sector accounting suppose some main adjustments regarding and prepared exposures draft to harmonize this problem